A STRATEGICAL APPROACH TO THE INTERCULTURAL COMMUNICATION: INTERCULTURAL EMPATHY (The Results of an Intercultural Communication Project) - Yağbasan, Mustafa; Demirbağ, İsmail (Gümüşhane Üniversitesi, 2017)
The earth continues to make tracks for a new social order. It is possible to describe this new order as “intercultural life”. Likewise, until the late history, it seems that the intercultural confrontations which are only related to the approval of the political power and sometimes emerged with only diplomatic or ideological considerations have already become legal through “new communication technologies” and then spread to the base as intercultural transitions and intimacies. In fact, this new social process that can also be defined as the“ meeting of cultures” may sometimes occur virtually by means of the electronic channels and sometimes in the form of natural and actual meetings (thanks to the human circulations with disappearance of the borders). It can be supposed that this metamorphism (metamorphosis) corresponding to a humanist perspective may also really intervene in having some social troubles. However, the unexpected confrontations in the unknown cultural environments (with the contribution of sensations and experiences whose objectivity is questionable) can lead to concerns (anxieties) or prejudices in the mind of the individuals. The countries, Germany and Turkey, form the population built on this basic hypothesis. In this sense, it has been tried to be tested by sampling the ‘intercultural communication project’ carried out under the name of ‘Cities in Transition’ hosted by Madgeburg University and Fırat University in 2012, and based on the method of the aforesaid “anxieties” and “in-depth interview” and with the emphatic point of view. In this study confined to the communications students, it has been reached to the results attributing importance strategically.

Yerküre, yeni bir sosyal düzene doğru hızla yol almaya devam etmektedir. Bu yeni düzeni “kültürlerarası yaşam” şeklinde ifade etmek mümkündür. Zira yakın tarihe kadar sadece siyasal erkin iznine tabii olan ve bazen de sadece diplomatik veya ideolojik mülahazalarla gerçekleşen kültürlerarasındaki karşılaşmalar, “yeni iletişim teknolojileri” marifetiyle artık meşrulaşarak, kültürlerarası geçişler ve yakınlaşmalar şeklinde tabana yayılmış gibi görünmektedir. Aslında “kültürlerin buluşması” şeklinde de ifade edilebilecek olan bu yeni sosyal süreç bazen elektronik mecralar yolu ile sanal olarak, (sınırların ortadan kalkmasıyla yaşanan insan sirkülâsyonları sayesinde) bazen de tabii ve fiili karşılaşmalar şeklinde gerçekleşebilmektedir. Hümanist bir perspektife tekabül eden bu metamorfizmin (başkalaşım) aslında bazı sosyal sorunların yaşanmasına da aracılık edebileceği varsayılabilir. Zira bilinmedik kültürel ortamlardaki ani karşılaşmalar (nesnelliği şüpheli olan duyum ve deneyimlerin de katkısıyla) bireylerde kaygıların veya önyargıların oluşmasına neden olabilmektedir. Bu temel hipotez üzerine inşa edilen araştırmanın evrenini Almanya ve Türkiye oluşturmaktadır. Bu bağlamda Magdeburg Üniversitesi ile Fırat Üniversitesinin ev sahipliğinde 2012 yılında “Cities in Transition” (geçişlerde şehirler) adı altında gerçekleştirilen “kültürlerarası iletişim projesi” örneklem alınarak söz konusu kaygılar ‘derinlemesine mülakat’ yöntemine dayalı olarak ve empatik bir bakış açısıyla test edilmeye çalışılmıştır. İletişim öğrencileri ile sınırlı tutulan bu çalışmada, stratejik açıdan önem atfedilebilecek bulgulara ulaşılmıştır.
KÜLTÜRLERARASI İLETİŞİME STRATEJİK BİR YAKLAŞIM: KÜLTÜRLERARASI EMPATİ (Bir Kültürlerarası İletişim Projesinin Sonuçları)